Epidemiological profile of workers with musculoskeletal disorders of a supermarket company - Marcia Benites da Silva; Caren Lara Martins Picasso; Miriam Pilla Rosito
AbstractIntroduction The epidemiological profile is considered a sensitive indicator of living conditions and the disease process. The musculoskeletal disorders are the most common causes of pain and can lead to disability or restriction of daily activities. These disorders take the name of RCT/OWRD when they are associated with work activities and may be associated with risk conditions at work.Objectives To describe the epidemiological profile of supermarket workers with musculoskeletal disorders under treatment at a physiotherapy clinic in the city of Porto Alegre, Brazil.Methods This was a cross-sectional, observational study which used retrospective data collected from 360 records of patients treated from January 2010 to December 2011 in a physiotherapy clinic that provides health services for a supermarket chain.Results There was a predominance of females (73.9%), aged 30-39 years (35.1%); 63.0% reported being single and 73.4% lived in Porto Alegre. The most commonly reported occupation was cashier (31.2%). The main reasons for referral to physiotherapy treatment were low back pain (21.4%), neck pain (19.7%), pain (16.1%), subacromial bursitis (13.9%) and back pain (12.2%). Among the signs and symptoms 95.8% of the sample reported pain in chronic phase.Conclusion The prevalence of musculoskeletal pain was high in this group. The presence of pain can disable the worker for daily activities and physiotherapy becomes the therapeutic procedure of choice for their rehabilitation.